USING ONOMATOPOEIA IN COMIC TO IMPROVE READING SKILL - Eliza, Tiara (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2022)
In the field of second language teaching, reading has been one of the most neglected areas in the classroom. Teaching reading for some educators is kind of a challenge. They already made plans to teach with great scheme of their lesson plan and fabulous exercises exactly what the curriculum asked them, but in the application, they were failed. This study was meant to find out how to improve reading skill by using onomatopoeic expression in comic and to describe some challenges in using comic as a media of teaching and learning process. This study used a qualitative descriptive analysis. The participants were taken from the students in private classes. The research data is collected by using test (test after the first treatment and test after the second treatment) and by observation for collecting data on the students’ motivation in improving reading skill using onomatopoeic expression. The data were analyzed by using the descriptive analysis. The result showed that in the first cycle, the students’ average was 65.8, then, on the second treatment, the students’ average increase to be 75.9. It can conclude that teaching reading by using onomatopoeic expression in comic can be used as media to improve students’ reading skill.